Rich brother rich sister : two different paths to God, money and happiness - Kiyosaki, Robert T., 1947-; Kiyosaki, Emi. (New York : Vanguard Press, 2009)
Two Japanese Americans combines the true life stories of Robert Kiyosaki and his sister [Barbara] Emi into one book that attests to a belief in the power of purpose, the importance of action, and the ability to overcome all obstacles in a quest for wealth, both financial and spiritual.'While Robert took the path of war during the Vietnam era, Emi took the path of peace, exploring alternative and spiritual journeys,' and is now known by her Buddhist ordination name, Bhikshuni Tenzin Kacho. -- Publisher info
Keywords: Wealth; Faith; Happiness; Lifestyles; Alternative lifestyles